Women’s Empowerment in Punjab: An Analysis of Socio-Cultural Challenges - Hina Rashid (Sustainable Business and Society in Emerging Economies, 2022)
Purpose: Women empowerment is a rapidly growing theme that inspires women to feel courageous and do what they feel they cannot do. Women seem far behind compared to men when it comes to participation in different sectors, particularly the economy and politics. Punjab is the largest province of Pakistan in terms of population. Here, women are more in number than men and constitute 51.8% of the province’s total population. Despite being outnumbered, women lag far behind in terms of availability and access to resources and opportunities. A notable disparity can be observed in economic, political, and social sectors. The research intends to explore the key socio-cultural challenges that hinder the way of women towards empowerment in the province of Punjab.